2021
DOI: 10.1590/1806-9282.67.suppl1.20200793
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity practice during COVID-19 pandemic in patients with intermittent claudication

Abstract: OBJECTIVE: To describe physical activity habits and barriers for physical activity practice in patients with peripheral artery disease and claudication symptoms during Coronavirus 2019 (COVID-19) pandemic. METHODS:In this cross-sectional survey study, 127 patients with peripheral artery disease (59.8% men; 68±9 years old; and 81.9% had the peripheral artery disease diagnosis ≥5 years old) were included. The physical activity habits and barriers for physical activity practice were assessed through telephone int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 18 publications
(22 reference statements)
1
10
0
Order By: Relevance
“…Social isolation, because of the COVID-19 pandemic, has resulted in unintended consequences for the lifestyle and health of the population. 3 , 4 , 5 , 6 In the current study, the percentage of patients who self-reported practicing physical activity was similar between the two periods during the COVID-19 pandemic (28.3% [n=28] vs. 23.2% [n=23], P>0.05, respectively). We have previously demonstrated that the main barriers to physical activity practice in patients with PAD during the COVID-19 pandemic include social isolation, pain, injury or disability, lack of energy, and the need to rest because of leg pain.…”
Section: Discussionsupporting
confidence: 48%
See 4 more Smart Citations
“…Social isolation, because of the COVID-19 pandemic, has resulted in unintended consequences for the lifestyle and health of the population. 3 , 4 , 5 , 6 In the current study, the percentage of patients who self-reported practicing physical activity was similar between the two periods during the COVID-19 pandemic (28.3% [n=28] vs. 23.2% [n=23], P>0.05, respectively). We have previously demonstrated that the main barriers to physical activity practice in patients with PAD during the COVID-19 pandemic include social isolation, pain, injury or disability, lack of energy, and the need to rest because of leg pain.…”
Section: Discussionsupporting
confidence: 48%
“…We have previously demonstrated that the main barriers to physical activity practice in patients with PAD during the COVID-19 pandemic include social isolation, pain, injury or disability, lack of energy, and the need to rest because of leg pain. 5 It is important to point out that physical activity has been recommended to minimize the impacts of social isolation on health during the COVID-19 pandemic. 14 , 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations